The Solve Et Clause Repeats as a Mechanism for Managing Contractual Risks: Contours and Limits in Brazilian Law - Peçanha, Danielle Tavares (2024)
This essay is dedicated to the solve et repeat clause, which constitutes a legitimate mechanism for the positive allocation of contractual risks, through which the immediate feasibility of the performance is guaranteed, even if there are legal reasons that justify the possibility of non-compliance or delay in payment by the debtor. Inserted in the legitimate exercise of the negotiating autonomy of the contracting parties, this provision is subject to the control of legality and abusiveness, from which the relevance of its study is extracted, based on its contours and limits in Brazilian law, in light of constitutional legality.